Preparation and characterization of zinc oxide and titanium oxide polyethersulfone hybrid film photocatalysts for degradation of methyl orange - Mohd Hir, Zul Adlan (2018)
Environmental issues and scarcity of water reserves have led to the development of photocatalyst technology to recycle the polluted water. The photocatalyst is usually applied in powder form but suffers several drawbacks; (i) agglomeration which led to a decrease in photoactivity and (ii) difficult and costly recovery process. These problems could be overcome by immobilizing the catalyst on a support. With the aim to provide alternative solution to the solid–liquid separation problem, polyethersulfone (PES) was chosen as the support due to its stability against radicals produced during photocatalytic reaction. This work investigated the physicochemical characteristics of TiO2/PES, ZnO/PES and reduced TiO2 (rTiO2)/PES hybrid film photocatalyst prepared via phase inversion technique and reported, for the first time, its synergistic contribution in the field of photocatalysis. The films were characterized using Scanning Electron Microscopy (SEM), Energy Dispersive X-ray (EDX), X-ray Diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Atomic Force Microscopy (AFM) and UV-vis Diffuse Reflectance Spectroscopy (UV-vis DRS) analyses. XRD, SEM and EDX analyses revealed that the TiO2, ZnO and reduced TiO2 (rTiO2) were homogeneously dispersed and embedded onto the PES film. XPS and UV-vis DRS results confirmed the existence of interstitial site of TiO2 (458.2 and 463.9 eV), ZnO (1021.0 and 1043.8 eV) and rTiO2 (456.1 and 461.8 eV) with their respective band gap energy of 3.00, 3.15 and 2.85 eV. The films exhibited higher surface roughness and enhance hydrophilicity compared to PES film alone. The photoactivity of the films was evaluated with respect to methyl orange (MO) degradation under both UV and visible light irradiation. Emphasis was placed on the effect of catalyst loading, pH, concentration, number of films and recyclability study. The best film photocatalysts displayed pseudo first-order kinetics with almost 80% and 30% for PES–TiO2 (13 wt%), 100% and 56% for PES– ZnO (17 wt%), 76% and 55% for PES–rTiO2 (13 wt%) of MO removal under original condition against UV and visible light irradiation, respectively. A complete removal of MO was achieved at pH 2.0 for both PES–TiO2 (13 wt%) and PES–rTiO2 (13 wt%) and pH 5.8 for PES–ZnO (17 wt%). The degradation percentage decreased with increasing initial concentration of MO (5–20 mg/L) but increased with increasing number of films. The major active species were found to be •O2 – for both PES–TiO2 (13 wt%) and PES– rTiO2 (13 wt%) and h+ for PES–ZnO (17 wt%). The best films can be recycled for up to five times while retaining its stability and degradation efficiency without being subjected to any regeneration process. The degradation of palm oil mill effluent (POME) was monitored through chemical oxygen demand (COD) analysis with degradation percentage of 20%, 27%, 12% and 12%, 18%, 15% under UV and visible light irradiation, respectively with some reduction in American Dye Manufacturers’ Institute (ADMI) colour values.